Emerging biomarker in carcinogenesis. Focus on Nestin - Nowogrodzka, Katarzyna; Jankowska-Konsur, Alina (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Nestin is a protein belonging to class VI intermediate filaments, which is involved in organogenesis, cellular metabolism and cytoskeletal organisation. Originally found to be expressed in neuroepithelial stem cells, nestin is also expressed in other tissues. It plays an important role in the carcinogenesis and angiogenesis. Its increased expression in melanoma is associated with an aggressive course of the disease and poor prognosis. Research findings for non-melanocytic skin neoplasms are inconclusive. The aim of this paper was to systematize knowledge on the role of nestin in cancerogenesis. The authors focused in particular on the expression of nestin in skin malignancies, as well as on the potential role of nestin in the pathogenesis, prognosis and treatment of cutaneous neoplasms.